Reporting of Environmental Information by Transport Sector Companies in ESG reports - A Review of Practices Used - Iwona MAJCHRZAK; Marzena RYDZEWSKA (Communications of International Proceedings, 2025)
The purpose of this article is to examine the extent to which the environmental disclosures presented by listed companies in the transport sector in their ESG reports are aligned with the legal requirements in force in this area. The research conducted was qualitative and based on a content analysis method using a case study of listed transport sector companies. The research showed that the companies surveyed disclose environmental information to a very limited extent. Their scope and detail do not fully correspond to the requirements set out in the regulations. Furthermore, the place of presentation of information on the company's environmental impact and the detailed substantive content also varies, both between entities and within individual companies over the years. Thus, the degree to which these entities are prepared to meet the reporting obligations imposed on them varies. The research conducted is novel in that it indicates the extent of environmental information disclosed in ESG reports and allows us to determine the degree of preparedness of the surveyed entities to report this type of information. This research should be continued, including an extension to comparative analyses relating to environmental information published by companies in other industries whose activities also have a significant impact on the environment.
Keywords: sustainability report; environmental disclosures; transport companies